2020
DOI: 10.1159/000508041
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of the CPT in the Diagnosis of ADHD in Individuals with Substance Abuse: A Systematic Review

Abstract: Background: Early identification of attention-deficit/hyperactivity disorder (ADHD) in individuals with substance use disorders (SUD) is important because ADHD has an adverse effect on the development and course of SUD. Given the limited validity of self-report measures of ADHD in individuals with SUD, it is important to investigate the utility of the continuous performance test (CPT) in classifying ADHD in adults with SUD. Objective: This review aims to examine the quantitative similarities and differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 114 publications
(153 reference statements)
0
16
0
Order By: Relevance
“…In the CASP study, we collected data with a novel continuous performance test [23] in SUD patients with and without ADHD. Results from this study can be found in this special issue of European Addiction Research [24].…”
Section: Ongoing Projectsmentioning
confidence: 99%
“…In the CASP study, we collected data with a novel continuous performance test [23] in SUD patients with and without ADHD. Results from this study can be found in this special issue of European Addiction Research [24].…”
Section: Ongoing Projectsmentioning
confidence: 99%
“…The present study summarized the most recent research on the CCPT in adults. The reviews conducted to date on the CCPT in adults with ADHD have focused on comorbid substance abuse populations (Slobodin, 2020) and the performance of the CCPT in response to stimulant medications (Riccio et al, 2001). In addition, the present review investigated the reliability and validity of the CCPT for diagnosing ADHD in adults.…”
Section: Discussionmentioning
confidence: 99%
“…This review highlights the mixed findings on the use of the CCPT in adult ADHD diagnosis. Various reasons may explain why previous reviews on adult (Riccio et al, 2001; Slobodin, 2020) ADHD samples found mixed findings for the diagnostic utility of the CCPT for ADHD. Riccio and Reynolds (2001) noted that continuous performance tests are sensitive to general neurocognitive deficits, such as attention, which is a deficit in several disorders (e.g., ADHD, learning disorders, and depression).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations